2020
DOI: 10.1136/bjophthalmol-2020-316259
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with blindness three months following treatment for acute primary angle glaucoma

Abstract: AimsTo study the risk factors associated with blindness after treatment of acute primary angle closure (APAC), and to identify the critical time window to decrease rate of blindness.MethodsIn this multicentre retrospective case series, 1030 consecutive subjects (1164 eyes) with APAC in China were recruited. The rates of blindness were analysed up to 3 months after treatment of APAC. A logistic regression was used to identify the risk factors associated with blindness, including age, gender, distance to hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…TST is key to reducing blindness after APAC. Li reported that if a patient with APAC was treated within 4.6 h of the onset of an acute attack, the risk of blindness would be 1% or less (30). Our study showed that CDVA at presentation and postoperative follow-up were worse in the 2020 group than in the 2021 group, and the blindness rate caused by APAC during the epidemic in 2020 (21.87%) was twice that in the same period in 2021 (7.84%).…”
Section: Discussionmentioning
confidence: 99%
“…TST is key to reducing blindness after APAC. Li reported that if a patient with APAC was treated within 4.6 h of the onset of an acute attack, the risk of blindness would be 1% or less (30). Our study showed that CDVA at presentation and postoperative follow-up were worse in the 2020 group than in the 2021 group, and the blindness rate caused by APAC during the epidemic in 2020 (21.87%) was twice that in the same period in 2021 (7.84%).…”
Section: Discussionmentioning
confidence: 99%
“…When ocular hypertension is present in both eyes with an extra-shallow anterior chamber, which is a more common feature in Asians, it is easy to diagnose acute primary angle closure. The latter condition tends to be more usual in elderly people with short axial length[ 6 ]. Our patient's ocular axis was 22.6 mm in the right eye and 20.4 mm in the left eye (conforming to his established hyperopia), which is inconsistent with the clinical manifestations of primary angle-closure glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Regarding the current ophthalmic care in China, the average time from symptom to treatment was much longer than what we would expect in the western world. 4 Typical emergency treatment options for those with prolonged APAC, including topical and systemic intraocular pressure (IOP)-lowering medications, anterior chamber paracentesis, followed by laser peripheral iridoplasty and/or iridotomy, may not always be possible due to corneal oedema and fixed dilated pupil, and is not effective in the prolonged cases with extensive synechial angle closure. 3 5 Urgent surgical intervention such as cataract removal with or without an additional glaucoma procedure may be required.…”
Section: Introductionmentioning
confidence: 99%
“…All these factors lead to increased rates of blindness in patients with prolonged APAC. 4 Transscleral cyclophotocoagulation (TSCP) is a non-incisional laser procedure which can be performed easily by junior surgeons. TSCP has been described as a safe and effective treatment to provide some degree of IOP control in patients with APAC refractory to medical therapies before lens extraction in order to avoid emergent surgery in inflamed eyes and achieve a more favourable outcome.…”
Section: Introductionmentioning
confidence: 99%